2019
DOI: 10.3390/ijerph16245022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Sources of Second-Hand Smoking Exposure among Non-Smoking Pregnant Women in an Urban Setting of Vietnam

Abstract: Exposure to second-hand smoke (SHS) among non-smoking pregnant women can lead to adverse maternal and fetal outcomes. A cross-sectional study was performed from July to August 2016 among 432 pregnant women at Bach Mai Hospital, Hanoi, Vietnam, to assess the prevalence and sources of SHS exposure among non-smoking pregnant women. Socio-economic characteristics and information regarding SHS exposure of participants were collected. Multivariable logistic regression was employed to identify associated factors. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…Most participants were living in urban areas (86.1%). The rate of pregnant women at 30-37 gestation weeks and <30 gestation weeks were 46.3% and 37.7%, respectively [32]. In addition, data on the main sources of information about SHS for pregnant women indicated that television was the primary source, following by news/magazines, and the internet; leaflets were the least common ones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most participants were living in urban areas (86.1%). The rate of pregnant women at 30-37 gestation weeks and <30 gestation weeks were 46.3% and 37.7%, respectively [32]. In addition, data on the main sources of information about SHS for pregnant women indicated that television was the primary source, following by news/magazines, and the internet; leaflets were the least common ones.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that rates of SHS exposure among pregnant Vietnamese women have remained high, with similar patterns occurring in other low-and middle-income countries [29][30][31]. According to a recent study in 2019, the rate of pregnant Vietnamese women who endured SHS exposure in their lifetime was 92.6%, and during the last 30 days of pregnancy, the rate was 64.5% [32], relatively high. However, data on KAP regarding SHS in this population are lacking.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“… 7 There was a high proportion of second-hand smoking (SHS) exposure among non-smoking pregnant women in Vietnam. 8 In Vietnam, being male and having hazardous drinking habits and a poor quality of life were all factors that were significantly associated with smoking status. 9 The primary reason for smoking relapse was surrounding smoking environments.…”
Section: Introductionmentioning
confidence: 99%
“…Do [17] acknowledges limited evidence of SHS for these women despite the public health consequences. While Ngo reports SHS exposure rates in Vietnam of over 90% among pregnant women, other international comparisons range from 20% to 79%, but the included studies were carried out before 2010 [18]. Bloch reports SHS exposures internationally from 6.1% to almost 80% [19]; however, Siddiqi acknowledges a lack of evidence and the need for more studies [20].…”
Section: Introductionmentioning
confidence: 99%